ESTEEM SOCIETY : MENAKAR MODE KONSUMERISME BARU DALAM FOOD PHOTOGRAPHY DI KOTA MALANG - Muhammad Iqbal Tawaqkal (Jurnal Desain Komunikasi Visual Asia, 2022)
The development of social media is increasingly growing rapidly. Not a few people feel that, especially the people in Malang. The development of social media has a significant impact on the community in Malang. Indirectly, the various impacts that emerge begin to slowly change the style of community patterns in using social media in everyday life. The creation of new consumerism in the social fabric can be found with the activity of taking pictures and posting food / drinks before consuming them. The majority people in Malang, of course, have their own reasons and background to do so.This research has the focus of the problem, namely: 1) How is the new mode of consumerism created in the phenomenon of food photography to the people of Malang? A qualitative approach was used in the process of extracting data in this study. Based on the purpose, this research is a descriptive research type. This study uses data mining techniques in the form of open and in-depth interviews, observations, and documentation taken in the form of audio and photographs. The location of this research was conducted in Malang City, especially in various caffees, such as Roketto Coffee and Amstirdam Coffee. The process of data analysis in this research is to do data reduction, data display, and verification. While the validity of the data is examined using source triangulation techniques, theories, methods, and investigators. From the results of research that has been obtained, that actually the people in Malang have assumptions and opinions that are quite different and unique. In today's society, it is rarely seen that those who before eating / drinking raise their hands to pray first (old consumerism). The creation of new consumerism in this society is increasingly apparent with their activities before eating / drinking raising their hands while holding the camera to take pictures and post on social media (new consumerism). In this phenomenon, consumerism can only be categorized into two different typologies of society. Of the two typologies, the Society has a different esteem. Some people think that photographing and posting food / drinks is just satisfying a hobby. But, some others consider it, as an area to become a profession.